2019
DOI: 10.3126/jcmc.v9i4.26894
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic sensitivity pattern in urinary tract infection among adults in central part of Nepal

Abstract: Background: Urinary tract infection (UTI) is characterized by pathological invasion of the urinary tract by microorganisms. Majorities of organisms causing UTI are gram negative bacteria, most common of which is E. coli. Urine culture and sensitivity test is used to isolate the organism and to identify the susceptible drug of choice for appropriate treatment. This hospital-based study was carried out to analyze the spectrum and antibiotic susceptibility of microorganisms causing UTI. Methods: A retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
0
0
Order By: Relevance
“…The results of this current study revealed that females were more susceptible to UTIs than males ( p > 0.05). This finding is in alignment with some studies conducted by other researchers [ 39 , 40 , 41 ]. The increased incidence of UTIs in females may be due to favouring anatomic factors, hormonal changes and urodynamic disturbance occurring to age [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results of this current study revealed that females were more susceptible to UTIs than males ( p > 0.05). This finding is in alignment with some studies conducted by other researchers [ 39 , 40 , 41 ]. The increased incidence of UTIs in females may be due to favouring anatomic factors, hormonal changes and urodynamic disturbance occurring to age [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, in our research, it was found that 44.7% of females had a significant growth of bacterial uropathogens, while only 33.5% of males showed a similar growth. Notably, these figures are higher than those reported in a study conducted in Nepal, where only 28% of females and 17% of males had bacterial uropathogens in their urine culture [11].…”
Section: Discussioncontrasting
confidence: 73%
“…1 It is estimated that globally, UTI accounts for 150 million cases per annum and 25% of all infections. 2,3 The common pathogens responsible for UTI are Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, Proteus mirabilis, Pseudomonas aeruginosa, Enterococcus faecalis and Enterobacter cloacae. 4 Enterococcus were considered as a low grade pathogen previously but now they have switched to opportunistic nosocomial and community acquired pathogen.…”
Section: Introductionmentioning
confidence: 99%